2021
DOI: 10.1007/s00348-021-03148-0
|View full text |Cite
|
Sign up to set email alerts
|

Flow measurements in the wake of an adhering and oscillating droplet using laser-Doppler velocity profile sensor

Abstract: The removal of droplets on surfaces by an (air-) flow is relevant, e.g., for cleaning processes or to prevent corrosion or damage of electronic devices. Still the condition for droplet movement is not fully understood. Droplets start to move downstream at a critical (air-) flow velocity vcrit. For increasing flow velocity, this process is related to a strong oscillation of the droplet. This oscillation is supposed to be a key mechanism for the onset of droplet movement in conjunction with the flow field around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Experimental investigations confirmed that the droplets featured two oscillation modes, forwardbackward and upward-downward [11] when the airflow velocity was lower than the critical detachment value. Vertical oscillations were analysed in time ranges given by a minimal variation of the average height (<4%) but sufficiently wide to furnish statistically adequate samples (>100ms).…”
Section: Resultsmentioning
confidence: 78%
“…Experimental investigations confirmed that the droplets featured two oscillation modes, forwardbackward and upward-downward [11] when the airflow velocity was lower than the critical detachment value. Vertical oscillations were analysed in time ranges given by a minimal variation of the average height (<4%) but sufficiently wide to furnish statistically adequate samples (>100ms).…”
Section: Resultsmentioning
confidence: 78%
“…In the present work, a recently introduced commercial ILA R&D LDV-PS system with an integrated 5 MHz Bragg shift is employed, which was recently shown to allow measurements of all three velocity components based on trigonometric reconstruction in a laminar Couette-like oil flow in a clutch test rig (Leister et al, 2022). The commercial measurement system has furthermore been successfully applied to measure the turbulent flow in the wake of a droplet with a spatial resolution of 10 µm (Burgmann et al, 2021) and the flow topologies appearing in rotary pumps used for blood (Strauch et al, 2022). The two above-mentioned studies, therefore, present the LDV-PS as a promising diagnostics tool for non-intrusive measurements in turbulent flows and, especially, for the determination of the velocity gradient in the viscous sublayer, which would in turn offer the desired possibility of direct local wall shear stress measurements.…”
Section: Related Work Using the Ldv-psmentioning
confidence: 99%
“…It must be noted that an important physical phenomenon here is the occurrence of oscillations, which are rooted in the concurrent effect of inertia and surface tension 8,66,67 . In order to prevent strong droplet oscillations in this section, first, the gravity is linearly increased from zero to g = 9.81m/s 2 with a slope of g/τ r while the tilting angle is kept zero.…”
Section: A Water Droplet On Tilted Solid Substratementioning
confidence: 99%